Economics of Digitalization, Cryptoeconomics, Tokeneconomics - The Challenges to Economic Theory - Iliev, Petkan (Research Papers, 2024)
In this paper, we further develop the concept of the difference between the economics of digitalisation and what some authors call “digital economics”, which uses digital transformation, digital models and concepts to bring technological element in the analysis of economic systems or behavior. The rapid development of digital transformation in all socio-economic spheres gives rise to the need to further develop this theoretical model due to the fact that in the rapidly developing world of blockchain technology new innovations and trends are generated every year that reshape industries. The answer to this is cryptoeconomics and tokennomics.
Keywords: Digital economy; Digital economics; Tokenecomics; Cryptonomics